Apparatus for manufacturing glass and method for manufacturing glass using the same - RIM, JUNG HWAN; LEE, JISEOB; KIM, YOUNG SIK; KIM, KIL HO; NA, SANG OEB; HAN, JONG KYOENG (2016)
The invention provides an apparatus for manufacturing glass and a method for manufacturing glass using the same. The invention can effectively remove the surface glass before the surface glass is put into a modeling device so as to manufacture a smooth glass substrate used for the displayer. The product produced by the invention does not have the optical distortion and the ripple on the mechanical surface. The surface glass is generated due to the evaporation of the low density volatile particles (like boracic acid) in the process of manufacturing the glass where the combustion chamber is arranged and the glass surface is freely evaporated.